MANAJEMEN PEMBELAJARAN PONDOK PESANTREN : Studi Di Pondok Pesantren Miftahul Huda Segeran Juntinyuat Indramayu - Arwani Arwani; Muchlisin Muchlisin (Khulasah : Islamic Studies Journal, 2023)
Miftahul Huda Islamic Boarding School Soon Juntinyuat Indramayu is a non-formal educational institution that combines traditional systems with modern systems. In its implementation, the Miftahul Huda Pesantren Soon Juntinyuat Indramayu uses learning management that is centered on kyai. Learning management in Islamic boarding schools is seen as a necessity in order to survive amidst competition and globalization, as well as as a foundation for future development. The success of learning management in Islamic boarding schools is a benchmark in the management of Islamic boarding school education. There are three problems in this research, namely: (1) how to plan learning at the Miftahul Huda Pesantren Selamatn Juntinyuat Indramayu, (2) how to implement learning at the Miftahul Huda Pesantren Selamatn Juntinyuat Indramayu, (3) how to evaluate learning at Miftahul Huda Islamic Boarding School Soon Juntinyuat Indramayu. This research method uses a qualitative descriptive approach. The research subjects were the founding ustad, managing ustad, and santri. The object of this research is the learning management of the Miftahul Huda Islamic Boarding School, Pesantren Juntinyuat Indramayu. The data collection method uses interviews, observation and documentation methods. The results of the research show that the Miftahul Huda Pesantren Soon Juntinyuat Indramayu has implemented learning management starting from planning, organizing, preparing personnel, directing and supervising learning activities. It's just that planning and determining teaching materials (books) and evaluation are still centered on kyai policies. Learning management at Islamic boarding schools can be carried out according to correct procedures, but it still requires the "blessings" of the Kyai so that Islamic boarding school education can be successful in accordance with the goals set by the Islamic boarding school. As a suggestion for the implementation of learning management, Islamic boarding schools can create syllabi and lesson plans in accordance with their principles and needs by training teachers/clerics. Islamic boarding school administrators need to prepare standard and systematic lesson schedules for each generation, so that the teaching and learning process takes place well. Keywords: Management, Learning, Islamic Boarding School